The role of the legal culture in the development of local government: the experience of the Republic of Kazakhstan and Poland (Journal of actual problems of jurisprudence, 2018)
This article discusses some of the problems of formation of legal culture and consciousness of Kazakh society in modern times. Reveals the relationship of legal culture with the legal values. Legal values is the most important for the state, society and the individual regulations, rules and ideas. In legal values embodied ideal notions of fair, decent, humane world order. The article analyzes the impact of the legal culture in the development of the system of local government in Poland. It is noted that the process of implementing a new political and legal reform local government was resolved by an independent organization «Fund for the development of local democracy. «Concluded that Kazakhstan needs to develop non-governmental organizations and other civil society institutions.Key words: legal culture, transformation of legal consciousness, legal values, the reform of local self-government, self-organization of citizens, the balance of interests of the state and society.